Liberty and the News - Lippmann, Walter (mediastudies.press, 2020)
Liberty and the News was published a century ago, the young Walter Lippmann's fifth book. The slim volume merits a fresh read in our post-truth moment. "In an exact, sense," Lippmann writes, "the present crisis of western democracy is a crisis in journalism." For Lippmann, liberty constitutes a method, not a series of prohibitions and permissions. The book's aim is to identify and examine potential reforms to boost the reliability of news-a project as relevant today as it is unfinished. Liberty and the News is republished in this mediastudies.press edition with a new introduction by Sue Curry Jansen.